Fostering Work Ability Among Menopausal Women. Does Any Work-Related Psychosocial Factor Help? - Viotti S; Guidetti G; Converso D; Sottimano I (Dove Medical Press, 2020)
Sara Viotti, Gloria Guidetti, Daniela Converso, Ilaria Sottimano Department of Psychology, University of Turin, Turin, ItalyCorrespondence: Gloria Guidetti Via Verdi 10, Turin 10124, ItalyEmail gloria.guidetti@gmail.comIntroduction: Due to the aging workforce, it will become even more common for organizations to count, among their employees, women who are dealing with menopause. To date, no knowledge is available regarding the work ability among menopausal women. With this view, the aim of the present study was to identify work-related psychosocial factors associated with work ability in a sample of menopausal working women.Methods: A self-report questionnaire was administered to 1069 menopausal women employed as administrative officers in the Italian public sector. The study design was cross-sectional.Results: Work ability was found to be negatively associated with family–work conflict (β = − 0.21, p = 0.0001) and positively associated with health-oriented organizational climate (β = 0.12, p = 0.0001), job autonomy (β = 0.08, p= 0.006), and skill discretion (β = 0.08, p= 0.048). Conversely, work ability did not show significant associations with job demands, flexible working hours, and social support.Discussion: From a practical point of view, our study identifies various areas of intervention that could foster job sustainability during menopause. In particular, our findings suggest that, to improve women’s job sustainability across their entire work-life span, it may be crucial to develop organizational policies, training, and activities specifically dedicated to sustaining menopausal women’s well-being.Keywords: work ability, menopause, aging workforce, women, work-related psychosocial factors